Getting Beyond “CRAAP”: Scientific Literacy in FYW and WAD - Erica Duran; Lauren M. Springer (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
While first-year writing (FYW) programs often bear the responsibility for teaching students to write across the disciplines (Downs and Wardle), too often students restrict the concepts learned in FYW to the humanities, or even worse, a single class. Moreover, students frequently complete research assignments in FYW which restrict them to scholarly or peer-reviewed sources, hindering their ability to learn how to assess popular sources. This can be especially problematic with scholarly STEM sources, which are laden with unfamiliar technical terms. Although the writing and research skills learned in FYW are often intended to be interdisciplinary, FYW faculty have opportunities to make these courses more relevant and useful to students interested in pursuing STEM majors or careers. We argue FYW is a critical space, allowing us to help students learn how to find, assess, and process scientific information, while simultaneously teaching students how the rhetorical situation (i.e., purpose and audience) is important outside of humanities; since future scientists are tasked, now more than ever, with presenting their information to non-experts in an increasing number of arenas, often competing with pseudoscience. Therefore, our article includes ways to build a STEM-themed FYW course and provides instructors with assignments emphasizing both popular and scholarly sources for all majors, helping demonstrate the value of writing about the sciences in various mediums. Ultimately, FYW provides a unique space where instructors have the chance to help both STEM and non-STEM majors prepare to effectively write and research in today’s ever-changing world.